2417. Risk Factors, Response to Empiric Therapy, and Healthcare Utilization Among Children With UTI Due to Extended Spectrum β-Lactamase-Producing Enterobacteriaceae. (26th November 2018) - Dasgupta-Tsinikas, Shom; Zangwill, Kenneth; Van, Tam; Friedlander, Scott; Yeh, Sylvia H
Abstract: Background: There are few data on risk factors, chosen therapy and healthcare utilization among US children with extended spectrum β lactamase-positive urinary tract infection (ESBL UTI). We performed a multicenter case–control study on childhood ESBL UTI from November 2014 to February 2017; herein we present preliminary data from a single Los Angeles County hospital. Methods: We defined UTI per 2011 AAP guidelines and ESBL per CLSI specifications. ESBL(−) UTI controls were matched by sex and age. Descriptive and matched univariate analyses on medical record data (up to 6 months after index culture) were performed. Results: Among 893 urinary Enterobacteriaceae isolates, 28 were ESBL(+), of which 23 were included: 13 girls, 0–5 year olds; 4 girls, ≥6 year olds; and 6 boys, 0–5 year olds. Prior hospitalization (55 vs. 78% for cases vs. controls, respectively), prior receipt of systemic antibiotics (55 vs. 38%), index hospitalization (39 vs. 20%), mean length of stay (3.9 vs. 3.6 days), and medical comorbidity (44 vs. 56%) did not differ significantly between groups. As well, several biosocial risk factors were similar in both groups, including: race, ethnicity, non-English-speaker, access to public benefits, international travel, non-US-birth, domestic violence/child abuse/neglect, and housing insecurity. Of cases and controls receiving any therapy, 16% and 96%, respectively, got empiric antibiotics to which the isolate was susceptible ( P = 0.001). After culture results were available, only 39% of cases and 96% of controls received effective agents ( P = 0.00002). Forty-two percent of cases had clinical improvement (within a mean of 2–3 days), vs. 43% of controls. Total treatment duration did not differ, and no deaths were recorded. In the 6 months after index UTI, groups did not differ in number of clinical encounters, proportion with documented follow-up, repeat urine tests, receipt of additional therapy, or prophylactic antibiotics. The proportions undergoing any GU-specific imaging were similar (62 vs. 47%), but this imaging included modalities with ionizing radiation in 4 cases vs. none of the controls ( P < 0.05). Conclusion: Our data suggest that clinical improvement occurs with initial (and potentially ineffective) empiric regimens, regardless of ESBL phenotype. The finding of more ionizing radiation exposure warrants additional study. Disclosures: All authors: No reported disclosures.